The Effect of Financial Literacy and the Application Of Financial Records On the Performance Of MSMEs (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of financial literacy and the application of financial records on the performance of MSMEs in Bojonegoro District, with a focus on angkringan businesses. This research uses quantitative methods with descriptive and associative approaches. Data were collected through questionnaires and analyzed using SPSS. The results showed that the application of financial records had a significant effect on the performance of MSMEs while financial literacy did not show a significant effect. Simultaneously, financial literacy and financial records have a significant effect on performance. This research confirms the importance of good financial management through structured records to improve the sustainability of MSME businesses, especially in the context of micro businesses such as angkringan.